Passive cooling methods; a comparative study of traditional Malay house and semi-detached modern homes - Ramlan, Rania Yushinie; Abdul Talib, Yuhainis; Husain, Fazidah Hanim (2025)
Traditional Malay houses incorporate passive cooling techniques, such as elevated floors and wide verandas, which naturally regulate indoor temperatures and reduce reliance on mechanical systems. However, modern housing, influenced by urbanization and globalization, risks eroding Malaysia's cultural heritage and indigenous architectural principles. As urban areas increasingly favor modern designs, it is crucial to assess how these newer homes can offer similar cooling benefits while maintaining sustainability. Modern houses often depend on air conditioning, leading to higher energy consumption and environmental impact. This study aims to compare passive cooling methods in traditional Malay houses with those in modern semi-detached homes in Malaysia. Fieldwork measurements and observations serve as the primary research tools, focusing on traditional Malay houses in Perak and modern homes in Selangor. The study examines factors such as building orientation, ventilation rates, types, and material usage to highlight the effectiveness of traditional cooling methods. It also explores how these strategies could be integrated into contemporary housing designs. Ultimately, the research provides insights into how incorporating traditional passive cooling techniques into modern homes can enhance thermal comfort while reducing energy consumption. This study aims to inform sustainable architectural practices, preserve cultural heritage, and guide policies for more environmentally friendly housing solutions in tropical climates like Malaysia.